Substantial labor market effects of the residency status: How important are initial conditions at arrival for immigrants? - Eric Schuss (Deutsches Institut für Wirtschaftsforschung (DIW), 2017)
This paper uses information on the legal status upon arrival to study long-term labor market effects, whereas selection and potential outmigration are taken into account by a large set of methods. I find that immigrants arrived with a job commitment in Germany achieve a longterm income advantage of 18.6% relative to other migrant groups, while language skills and ethnic networks can be excluded as transmission channels. Thus, a better linkage between job vacancies in the host country and the labor supply of potential migrants in the home country prevents mismatches and unrealistic expectations of potential migrants towards the host country.
Keywords: F22; J61; K37; 330; Residency status; Migrant selection; Initial conditions of immigrants